Digital Literacy and Social Media Awareness among Adolescents: A Case Study on Adolescents in Serang City - Nurjuman, Husnan; Priana, Ronny Yudhi Septa (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
The development of digital technology has encouraged teenagers to become active users of social media in their daily lives. However, the high intensity of use is not always accompanied by adequate awareness of ethics, information security, and the social impact of digital activities. This study aims to analyze the level of awareness of teenagers in using social media and how digital literacy affects their mindset and behavior in the digital space. This study uses a qualitative approach with a case study method in Serang City. Data were collected through in-depth interviews with 12 teenagers aged 15–18 years from various educational backgrounds, as well as observations of their social media usage habits. Data analysis was carried out thematically to identify patterns of awareness, understanding of digital risks, and reflective abilities in interacting on social media. The results of the study show that most teenagers have a functional understanding of social media, but have not shown critical awareness of its impact, both on themselves and their social environment. The digital literacy they have tends to be technical and comes from personal experience or peer environment, while support from family and formal education is still minimal. This study recommends the importance of integrating digital literacy education into the school curriculum and strengthening the role of the family in forming a healthy and responsible social media culture